2005
DOI: 10.1017/s002202990500138x
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced and other chemical changes in commercial UHT milks

Abstract: The properties of commercial directly and indirectly heated UHT milks, both after heating and during storage at room temperature for 24 weeks, were studied. Thermally induced changes were examined by changes in lactulose, furosine and acid-soluble whey proteins. The results confirmed previous reports that directly heated UHT milks suffer less heat damage than indirectly heated milk. During storage, furosine increased and bovine serum albumin in directly heat-treated milks decreased significantly. The changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 16 publications
11
53
1
4
Order By: Relevance
“…Obviously, ESL milk samples of poor quality had been manufactured using an indirect UHT process that had been reported to be cheaper (regarding investment and production costs) and more energy-efficient compared to the direct UHT heating techniques using injection or infusion systems. On the other hand, directly UHT-treated ESL milk suffers less heat damage than indirectly heated milk and can therefore be used in the production of ESL milk as an alternative to modern microfiltration techniques [10,15,18,24,25].…”
Section: Comparison Of Acid-soluble β-Lgmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, ESL milk samples of poor quality had been manufactured using an indirect UHT process that had been reported to be cheaper (regarding investment and production costs) and more energy-efficient compared to the direct UHT heating techniques using injection or infusion systems. On the other hand, directly UHT-treated ESL milk suffers less heat damage than indirectly heated milk and can therefore be used in the production of ESL milk as an alternative to modern microfiltration techniques [10,15,18,24,25].…”
Section: Comparison Of Acid-soluble β-Lgmentioning
confidence: 99%
“…Furosine (NeoMPS PolyPeptide Laboratories Group, Strasbourg, France) was used as standard. Calibration (5,10,20,40,80, and 160 pmol·20 μL −1 injection volume) was performed by plotting peak area versus picomole of furosine. Concentrations of furosine were displayed as picomole, which were subsequently converted to the results given in mg·100 g −1 protein (Tab.…”
Section: Rp-hplc Analysis Of Furosinementioning
confidence: 99%
See 1 more Smart Citation
“…Sakkas et al (2014) suggested that this group of effects includes degradation of lactose to organic acids and formation of lactulose, denaturation of whey proteins, destruction of vitamins and enzymes, hydrolysis of proteins and lipids and disturbance of calcium/phosphorus equilibrium. Other effects include cooked flavor and nutritional value loss due to new substances formed by the Maillard reaction, which continues during storage of heated milks (Elliott et al, 2005). The effect of heat treatments on the components of milk has been described.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Browning et al (2001) e Elliott et al (2005), períodos de aquecimento e resfriamento prolongados durante o tratamento térmico podem resultar em pro dutos similares àqueles submetidos ao pro cesso de esterilização, visto os efeitos quí micos e biológicos agregados durante estas duas etapas. Portanto, é de se esperar que danos provoca dos pelo calor durante o tra tamento UHT sejam mais intensos em sis temas indiretos, quando comparado a sistemas diretos; uma vez que o dano causa do depende do tempo de exposição do produto ao calor (MORTIER et al, 2000).…”
Section: Resultsunclassified